Twelve Royal Stelas for Twelve Great Gods: New Discoveries at the Khinis Monumental Complex - Bonacossi, Daniele Morandi (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The article presents the latest results of the exploration conducted by Udine University’s Land of Nineveh Archaeological Project at the monumental site of Khinis, the imposing rock-art complex carved by Sennacherib at the head of the canal that the king named after himself (‘Sennacherib’s Canal’). The canal was part of the regional hydraulic network in the land behind Nineveh, which was built by the king in around 690 BC and commemorated by the so-called ‘Bavian Inscription’. The discussion focuses on the results of the recent investigations conducted at the Khinis quarry, which to date is the only Neo-Assyrian quarry that is known archaeologically, and on the rock reliefs that commemorate this unique memorial complex. A new rock-cut stela has been discovered by LoNAP, together with at least three previously unknown sculptured panels located along the Khinis cliff to the north of the monolith at the canal gate, one of which still conserves part of its sculpted decoration. The extensive use of state-of-the-art investigation and recording techniques, such as laser scanner survey, digital photogrammetry, 3D modelling, micro-relief recording, and UAV survey has made possible these and other significant new discoveries, resulting in substantial progress in our knowledge of this astonishing rock-art complex.